A comprehensive model integrating UTAUT and ECM with espoused cultural values for investigating users' continuance intention of using mobile payment - Zhao, Yuyang (2020)
Zhao, Y., & Bacao, F. (2020). A comprehensive model integrating UTAUT and ECM with espoused cultural values for investigating users' continuance intention of using mobile payment. In Proceedings of the 2020 3rd International Conference on Big Data Technologies, ICBDT 2020 (pp. 155-161). (ACM International Conference Proceeding Series). Association for Computing Machinery. https://doi.org/10.1145/3422713.3422754